Exploring the Impact of Indian and Non-Indian Holiday Schedules on Organizational Stress - Sharma, Soma; Oberoi, Sarbjit Singh; Band, Gayathri (Prabandhan: Indian Journal of Management, 2024)
Purpose : The study examined the impact of work-holiday schedules on organizational stress levels among Indian employees. We discovered the significance of sustainability reports in the minds of shareholders as a result of the increased importance of responding to global warming. Methodology : In the information technology and service industries, 193 workers were taken into consideration for this study; 100 of them observed the Indian Holiday Calendar (IHC), whereas 93 observed the Non-Indian Holiday Calendar (NIHC). The stress levels were measured using the AUDIT organizational stress screening tool, and any significant differences between the two groups were found using independent sample t-tests and correlational analyses. Findings : The findings demonstrated that workers who observed non-Indian holiday schedules had considerably higher levels of organizational stress, as indicated by lower work-life balance, holiday satisfaction, control, and organizational commitment toward workers, as well as higher levels of overload and job characteristics. Practical Implications : The study proved that organizational commitment acted as a mediator in reducing the negative impacts of stressors on employee wellness, with significant relationships between stress variables and organizational commitment measures observed in the IHC group. Originality : The study covered the effects of holidays, particularly on information technology, in contrast to earlier studies on organizational stress.